Pengetahuan Masyarakat Tentang Penggunaan Suplemen Vitamin untuk Meningkatkan Imunitas Tubuh Selama Pandemi COVID-19 di Kelurahan Klender, Jakarta Timur dan Kecamatan Panimbang, Banten - Maifitrianti Maifitrianti; Tuti Wiyati; Liesca Tria Novalita Zaid; Faridatul Bahiah (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Numerous Vitamins have an important role in maintaining the immune system and reducing the risk of COVID-19 infection. This study aimed to determine the level of public knowledge regarding vitamin supplements used during the COVID-19 pandemic to improve the immunity system and associated factors among the community of Klender sub-district, East Jakarta and Panimbang sub-district, Banten. This study was performed from August to October 2021. This study method was observational with cross sectional design.  Respondent’s data included home town, gender, age, education level, occupation, place of obtaining vitamin supplements, types of vitamin supplements consumed and sources of information regarding vitamin supplements were obtained from the questionnaire. Knowledge level assessment was carried out using a validated questionnaire. The respondents of this study were 804 people. Most of the respondents were aged 18-25 years (48.3%) and female (60.9%). The results showed that the majority of respondents had a good level of knowledge (70.5%). The bivariate analysis using the chi square test showed that the level of knowledge was related to the level of education (p<0.005).